TIRF imaging of Fc gamma receptor microclusters dynamics and signaling on macrophages during frustrated phagocytosis. (December 2016) - Lin, Jia; Kurilova, Svetlana; Scott, Brandon; Bosworth, Elizabeth; Iverson, Bradley; Bailey, Elizabeth; Hoppe, Adam
Abstract Background Recent evidence indicates that in addition to the T-cell receptor, microclustering is an important mechanism for the activation of the B-cell receptor and the mast cell Fcε-receptor. In macrophages and neutrophils, particles opsonized with immunoglobulin G (IgG) antibodies activate the phagocytic Fcγ-receptor (FcγR) leading to rearrangements of the actin cytoskeleton. The purpose of this study was to establish a system for high-resolution imaging of FcγR microclustering dynamics and the recruitment of the downstream signaling machinery to these microclusters. Methods We developed a supported lipid bilayer platform with incorporated antibodies on its surface to study the formation and maturation of FcγR signaling complexes in macrophages. Time-lapse multicolor total internal reflection microscopy was used to capture the formation of FcγR-IgG microclusters and their assembly into signaling complexes on the plasma membrane of murine bone marrow derived macrophages. Results Upon antibody binding, macrophages formed FcγR-IgG complexes at the leading edge of advancing pseudopods. These complexes then moved toward the center of the cell to form a structure reminiscent of the supramolecular complex observed in the T-cell/antigen presenting cell immune synapse. Colocalization of signaling protein Syk with nascent clusters of antibodies indicated that phosphorylated receptor complexes underwent maturation as they trafficked toward the center of the cell. Additionally, imaging of fluorescent BtkPH domains indicated that 3′-phosphoinositides propagated laterally away from the FcγR microclusters. Conclusion We demonstrate that surface-associated but mobile IgG induces the formation of FcγR microclusters at the pseudopod leading edge. These clusters recruit Syk and drive the production of diffusing PI(3, 4, 5)P3 that is coordinated with lamellar actin polymerization. Upon reaching maximal extension, FcγR microclusters depart from the leading edge and are transported to the center of the cellular contact region to form a synapse-like structure, analogous to the process observed for T-cell receptors.